Whole Brain Radiotherapy Versus Stereotactic Radiosurgery in Poor-Prognosis Patients with One to 10 Brain Metastases: A Randomised Feasibility Study. Issue 7 (July 2020) - Raman, S.; Mou, B.; Hsu, F.; Valev, B.; Cheung, A.; Vallières, I.; Ma, R.; McKenzie, M.; Beaton, L.; Rackley, T.; Gondara, L.; Nichol, A.
Abstract: Aims: A significant proportion of patients with brain metastases have a poor prognosis, with a life expectancy of 3–6 months. To determine the optimal radiotherapeutic strategy for brain metastases in this population, we conducted a randomised feasibility study of whole brain radiotherapy (WBRT) versus stereotactic radiosurgery (SRS). Materials and methods: Patients with a life expectancy of 3–6 months and between one and 10 brain metastases with a diameter ≤4 cm were enrolled at six Canadian cancer centres. Patients were randomly assigned (1:1) to receive either WBRT (20 Gy in five fractions) or SRS (15 Gy in one fraction). The primary end point was the rate of accrual per month. Secondary feasibility and clinical end points included the ratio of accrued subjects to screened subjects. This trial is registered with ClinicalTrials.gov (number NCT02220491). Results: In total, 210 patients were screened to enrol 22 patients into the trial; 20 patients were randomised between the two arms. Two patients did not receive treatment because one patient died and another patient withdrew consent after being enrolled. Patients were accrued between January 2015 and November 2017; the accrual rate was 0.63 patients/month. The most common reasons for exclusion were anticipated median survival outside the required range ( n  = 40), baseline Karnofsky Performance Score below 70 ( n  = 28) and more than 10 brain metastases ( n  = 28). The median follow-up was 7.0 months and the median survival was 7.0 months for all patients in the trial. The median intracranial progression-free survival was 1.8 months in the SRS arm and 9.2 months in the WBRT arm. There were five grade 3+ toxicities in the SRS arm and one grade 3+ toxicity in the WBRT arm; no grade 5 toxicities were observed. The cumulative rates of retreatment were 40% in the SRS arm and 40% in the WBRT arm. Conclusions: A randomised trial evaluating WBRT versus SRS in patients with one to 10 metastases and a poor prognosis is feasible. A slower than expected accrual rate and difficulties with accurate prognostication were identified as issues in this feasibility study. A larger phase III randomised trial is planned to determine the optimal treatment in this patient population. Highlights: The optimal management of brain metastases in patients with poor prognosis is controversial Randomised feasibility study of whole brain radiotherapy (WBRT) versus stereotactic radiosurgery (SRS) Patients had a life expectancy of 3–6 months and 1– 10 brain metastases 210 patients were screened to enrol 22 patients into the trial; 20 patients were randomised A randomised study of WBRT versus SRS is feasible in this patient population and a larger phase III trial is planned.